Accelerated Recovery After Renal Cell Carcinoma and Partial Nephrectomy With Lifestyle Modifications. Issue 6 (November 2021) - Moore, Scott
Objective and subjective recovery times following a partial nephrectomy may exceed 1 year if patients adhere to the current Western lifestyle. This case demonstrates the rapid recovery of a 59-year-old female who underwent a robotic partial nephrectomy and utilized lifestyle modifications as an adjunct to the treatment of a Stage T1a clear cell renal cell carcinoma. All 6 pillars of lifestyle medicine are incorporated into this patient's recovery plan, which successfully reduced her time to recovery after a partial nephrectomy. This case illustrates how modifications in diet, activity, sleep, stress management, social connectedness, and avoidance of risky substances may shorten recovery time after a partial nephrectomy and may serve as an example that providers can prescribe for patients recovering from other surgeries.